1981
DOI: 10.1093/nar/9.23.6571
|View full text |Cite
|
Sign up to set email alerts
|

Nudeotide sequence of the transforming early region Elb of adenovirus type 12 DNA: structure and gene organization, and comparison with those of adenovirus type 5 DNA

Abstract: The nucleotide sequence of the entire transforming early region of E1b of the highly oncogenic adenovirus type 12 (Ad12) DNA has been determined. The total sequence (3860 base pairs) encompasses the entire transforming early region E1 of Ad12 DNA. From the sequence for the E1b region of Ad12, and the transcription map of the E1b region (1, 2, 3, and this paper) the structure and gene organization of the early region E1b of Ad12 DNA were analyzed and compared with those of the E1b region in the non-oncogenic Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…The adenovirus type S (Ad5) E1B gene codes for 21,000-(21K) and 55,000-molecular-weight polypeptides (9), the Ad2 E1B gene codes for 19,000-and 53,000-molecular-weight polypeptides (1,43) and the Adl2 E1B gene codes for 19,000 and 58,000-molecular-weight polypeptides (9,26,36,44). The Ad5 or Ad2 E1B 19K polypeptide is important for maintenance of cell transformation (2, 11) and for protection of cellular and viral DNA degradation (31,43,47).…”
mentioning
confidence: 99%
“…The adenovirus type S (Ad5) E1B gene codes for 21,000-(21K) and 55,000-molecular-weight polypeptides (9), the Ad2 E1B gene codes for 19,000-and 53,000-molecular-weight polypeptides (1,43) and the Adl2 E1B gene codes for 19,000 and 58,000-molecular-weight polypeptides (9,26,36,44). The Ad5 or Ad2 E1B 19K polypeptide is important for maintenance of cell transformation (2, 11) and for protection of cellular and viral DNA degradation (31,43,47).…”
mentioning
confidence: 99%
“…4. Comparison of the deduced sequences with those in the corresponding regions of Adl2 DNA (19,20) indicated that these two fragments indeed contained the viral-nonviral junctions. As indicated in Fig.3, the left-hand junction was mapped at position 118 and the right-hand junction at position 3520, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…j, and k). The 50 K protein, encoded in a different reading frame and synthesized from the second AUG of the 2.2-kilobase E1B mRNA (2,9), could not be detected in the recombinantinfected cells. The results indicate that the material revealed by immunofluorescence consists of the 19K protein and that the 19K protein tends to form a condensed structure in the cytoplasm when its concentration is high enough.…”
Section: Figmentioning
confidence: 90%
“…The ElB gene encodes at least two proteins, with molecular weights of 19,000 to 21,000 (19K to 21K) and 50K to 55K (4,11,13,16,18). Recent sequence data on the AdS and Adl2 E1B regions have shown that there are three open frames for protein synthesis (2,9). In the case of Adl2, the first reading frame starts from ATG 1,541 and ends at TAA 2,030 and is capable of coding for the 19K protein.…”
mentioning
confidence: 99%